Thermodynamically consistent directional distortional hardening of Mg alloy: experiments and constitutive modeling. (2017) - Shi, Baodong; Peng, Yan; Pan, Fusheng; Sun, Jianliang; Yang, Chong
Abstract: As a lightweight structural metal, magnesium alloy exhibits strong anisotropy due to texture, which limits its use in energy-saving lightweight structures. This pronounced anisotropy cannot be captured by only classical isotropic or kinematic hardening due to the constant shape evolution of yield surfaces during plastic deformation. Therefore, the shape evolution of yield surface, known as distortional hardening is the main approach to characterize the anisotropic behavior of Mg alloy. Moreover, stress state is changing during forming process such as deep drawing, i.e., the loading path effect during plastic deformation cannot be ignored. Thus, focusing on loading path dependent directional distortional hardening of AZ31 Mg alloy, experimental investigation on the evolution of anisotropy is performed, moreover, a thermodynamically consistent constitutive model with distortional evolution of yield surface is employed to capture the anisotropic mechanical behaviour of AZ31 Mg alloy after model parameters identified with experiments.